Formação de nexos conceituais do número na educação infantil - Guimarães, Gabriela Guerreiro (2020)
This dissertation aims to analyze the conceptual nexuses of the natural numbers that are formed in children developed from Triggering Situations of Learning (SDA) provided in the context of Teaching Guiding Activities (AOE). In this context, it is necessary consider the role of interactions in the process in the process of forming conceptual nexuses of the number as content that are related to counting from SDA. The interactions are directly related to the work developed in an early childhood school in the countryside of São Paulo, in the year 2019 which involved 23 children, aged 5 and 6 years. The questions that led the research were defined as follows: What are the conceptual nexuses of the natural numbers that are formed in children while interacting in situations that trigger learning? What is the role of interactions in this process? The investigation is based on the assumptions of historical-cultural theory. The data were obtained from the development of SDA about the conceptual nexuses of the number, such as: numerical sense, correspondence one by one, grouping and numerical representation through the use of one game entitled: Quantitative hula hoops of colors and four games called: The deck of numerical sense; When the man didn't have to count; The problem of heroes and Numerical hula hoops. In this context, the SDA which are in the form of play and games are configured as an educational product, in which it was sought to enable predominantly playful learning in the context of early childhood education. As a result, the data obtained indicate that from the developed SDA, children were able to interact with the conceptual nexus of numbers, thus facilitating the apprehension of counting, in which it was found that in all children the conceptual nexus was formed, in some of them formed the conceptual nexus of correspondence one by one and, in the minority, the conceptual nexus of grouping. In this sense, the role of interactions highlights for its importance in the knowledge acquisition process, which provided greater appropriation by children of the conceptual nexuses of the number, facilitating learning and providing greater development for children.